The Law of Urban Growth and the Local Public Sector - John Hartwick (Queen's University, Department of Economics, 2013)
We set out a city as a price-taking exporter and importer with its own local structure (housing (land per household) and a local pure public good are produced endogenously). We impove labor efficiency in the export sector, observe a jump in the local wage, and trace the impact, particularly on production of the public good. In one case the population, output of the public good, and residential density expand (the law of urban growth) and in another, population, output of the public good and density contract.
Keywords: R23; H40; F43; 330; small open city; urban public sector; law of urban growth